1969
DOI: 10.1017/s001447970000449x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Fertilizers and Manure on Soil and Leaves of Cotton in Nigeria

Abstract: On a site in the Sudan Savanna, chemical properties of soils (except for phosphate) and the composition of cotton leaves were determined after fifteen annual treatments including dung, ammonium sulphate, single superphosphate and potassium chloride, in all combinations of three levels. In the soils dung increased C, N, cation exchange capacity, exchangeable Ca and Mg and pH, and decreased soluble Al and Mn; ammonium sulphate decreased pH, increased soluble Al and Mn, and decreased exchangeable Ca and Mg; potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 3 publications
3
16
0
Order By: Relevance
“…This is contrary to extrapolations from pot experiments, which suggest that unrealistically large levels of applications are required (Bessho and 281 Bell, 1992). These results confirm earlier field observations which showed that organic residues improved soil acidity under realistic field conditions (Bache and Heathcote, 1969;Kretzschmar et al, 1992;Le Mare, 1971). The positive effects in the soil is probably due to the freedom of the newly formed decomposition products to react with reactive A1 sites on mineral surfaces.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is contrary to extrapolations from pot experiments, which suggest that unrealistically large levels of applications are required (Bessho and 281 Bell, 1992). These results confirm earlier field observations which showed that organic residues improved soil acidity under realistic field conditions (Bache and Heathcote, 1969;Kretzschmar et al, 1992;Le Mare, 1971). The positive effects in the soil is probably due to the freedom of the newly formed decomposition products to react with reactive A1 sites on mineral surfaces.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Bessho and Bell (1992) estimate that 14 t ha -1 of a legume leaf or 42 t ha-l of barley straw were required to bring the activity of A1 in a red podsol to < 10 #M which are required for soya beans. Increased soil pH and decreased AI saturation have however been observed with lower rates of organic matter applications under field conditions in Nigeria, Tanzania and Niger (Bache and Heathcote, 1969;Kretzschymar et al, 1991;Le Mare, 1972). The causes of such pH increases are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…This study would recommend that a balanced fertilisation programme for weathered savanna soils with low CEC and bu †ering capacity is that which combines inorganic fertiliser with farmyard manure. This conclusion is in concord with the observation of Bache and Heathcote (1969), from the same long-term experimental Ðeld at Samaru, that soil chemical fertility constraint imposed by inorganic fertiliser : use for 19 years can be removed with farmyard manure. This 19-year-old prescription is not only applicable to the soil chemical fertility but also to the biological fertility criteria, even after 45 years of cultivation.…”
Section: Discussionsupporting
confidence: 80%
“…While studies continue to justify the beneÐts of inorganic fertiliser in savanna soils, complementary studies on the long-term e †ects of inorganic fertiliser on these poorly bu †ered soils are lacking. Bache and Heathcote (1969) showed that ammonium * Present address : School of Science, College of Education, Akwanga, Plateau State, Nigeria. " To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The soils are exposed to true high temperature and rainfall concentrated over a period of five months of the year. The prolonged use of chemical fertilizers especially N fertilizers gives rise to residual soil acidity and cation depletion (Jones, 1989, Bache andHeathcote, 1988). Under intensive agriculture now commonly practiced, soil fertility declines rapidly after a few years of continuous cultivation.…”
Section: Introductionmentioning
confidence: 99%